2002
DOI: 10.1002/ejsp.131
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a minority group identity out of shared rejection: the case of international students

Abstract: With a sample of international students, we investigated how perceptions of rejection by the host community are related to a sense of identification with other international students. Based on the rejection-identification model (Branscombe, Schmitt, & Harvey, 1999) we predicted that perceiving prejudice from the host university would be negatively related to psychological well-being. We expected that group identification with international students would mediate a positive effect of perceived discrimination on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
245
2
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(274 citation statements)
references
References 38 publications
20
245
2
7
Order By: Relevance
“…They found that being exposed to the same set of behaviors (i.e., supervisor's actions) in similar situations is likely to engender a similar response from each employee (i.e., trust or not in the same supervisor). This is not unlike the group responses from racial and gender minorities who have not experienced crucial events in life together but still develop similar responses and attitudes to such events (e.g., acts of discrimination; (Harrison, Price, & Bell, 1998;Schmitt, Spears, & Branscombe, 2003;Wright, Ursano, Bartone, & Ingraham, 1990). This does not preclude the possibility of individual differences but can instead help explain how different individuals can have similar reactions to events they did not experience together, which can in turn lead to a group response.…”
Section: Robot Identification and Emotional Attachmentmentioning
confidence: 94%
“…They found that being exposed to the same set of behaviors (i.e., supervisor's actions) in similar situations is likely to engender a similar response from each employee (i.e., trust or not in the same supervisor). This is not unlike the group responses from racial and gender minorities who have not experienced crucial events in life together but still develop similar responses and attitudes to such events (e.g., acts of discrimination; (Harrison, Price, & Bell, 1998;Schmitt, Spears, & Branscombe, 2003;Wright, Ursano, Bartone, & Ingraham, 1990). This does not preclude the possibility of individual differences but can instead help explain how different individuals can have similar reactions to events they did not experience together, which can in turn lead to a group response.…”
Section: Robot Identification and Emotional Attachmentmentioning
confidence: 94%
“…That is, social identifications buffers individuals against the negative consequences of stigma. RIM has been investigated in the context of ethnic minority identities (Branscombe et al, 1999;Latrofa, Vaes, Pastore, & Cadinu, 2009;Schmitt, Spears, & Branscombe, 2003), older people (Garstka, Schmitt, Branscombe, & Hummert, 2004), women (Schmitt, Branscombe, Kobrynowicz, & Owen, 2002) and people with physical disabilities (Fernández, Branscombe, Gómez, & Morales, 2012), but not, to our knowledge, in the context of mental illness groups.…”
mentioning
confidence: 97%
“…They must also engender systems that reproduce non-discriminatory policies, culture, and outcomes, and that offer opportunities for international students and scholars to overcome the deleterious effects of discrimination on their identity development. Schmitt, Spears, and Branscombe (2003) found through path analysis that international students' perception of discrimination engendered lower self-esteem and higher identification with other international students. They also found that identification with other international students led to an increase in self-esteem.…”
Section: Empirical Studies Of the Post-9/11 Eramentioning
confidence: 96%
“…Some other studies take the form of position papers and evaluative reports (e.g., Sigya & Hayward, 2003;APLU, 2004) that seek to advance or legitimize certain agenda or points of view. A few studies, however, baulk this general trend (e.g., Schmitt, Spears, and Branscombe, 2003;McKeown, 2003;Mpoyi & Thomas, 2003;Fullerton, 2005;Min-Hua , 2007;Poyrazli and Lopez 2007). In this literature review, I have covered each of these broad swathes, while giving primacy to the meta-analytical and research studies.…”
Section: Globalizationmentioning
confidence: 99%